Proposals for management of elderly care facilities: Experience reports professional gerontologist - Lima-Silva, Thaís Bento (2013)
The aim of this study was to present the first experiences of gerontologists professional practice gerontologist applied in the management of programs to the elderly. This study was descriptive study and examined the report of three professionals in Gerontology alumni about their involvement in the Living Center, Day Centre and the Long Term Institution (LPI). In this study the ability that most defined the gerontologist was the application of management tools, combined with actions that aimed well-being of older adults, families and the participation of different actors, including the community, a network of professionals and services.